Landslide potential is reviewed from the characteristics of the physical properties and strong shear of the avalanche material on the Arso-Waris National Road - Alex Sander; Duha Awaluddin Kurniatullah; Dewi Ana Rusim; Mujiati Mujiati; Bahtiar Bahtiar (Jurnal Indonesia Sosial Teknologi, 2024)
There are many landslide points on the Arso-Waris National road, so it is necessary to conduct research on the potential for landslides from the physical and shear strength properties. The analysis method uses Slope/W software from GeoStudio, using the Bishop and Fellenius analysis method. The results of the study on 4 points along the Arso-Waris section, showed that with a decrease in the value of the shear strength parameter, both the cohesion value (average decrease of 69.91%) and the value of the shear angle (average decrease of 92.77%) in the reverse analysis resulted in a decrease in the value of the safety factor score by 71.5% (Bishop Method) and 71.11% (Fellenius Method). The value of the smallest (critical) safety factor is 0,498, located at point 4 KM.105+193 in combination loading, by using Fellenius method. Changes in physical properties and shear strength have the potential to reduce safety factor so that there is potential for landslides.